The Impact of Ambidextrous Leadership on Employees’ Knowledge Sharing Behavior-Based on the Mediating Role of Trust - Liu, Yue (International Journal of Global Economics and Management, 2024)
With the development of social economy, knowledge has become an important resource for organizations to gain competitive advantage. The purpose of this study is to explore the relationship among ambidextrous leadership, knowledge sharing and trust, and to study whether trust plays a mediating role. Data resources are obtained through questionnaires, and SPSS and AMOS are used to conduct empirical tests. The results show that ambidextrous leadership has a positive impact on employees ' knowledge sharing behavior, and trust plays an intermediary role between them.